2016
DOI: 10.5455/ajvs.192160
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sarcocystis Species Based on Traditional and Molecular Methods in Imported Frozen Buffalo Meat in Egypt

Abstract: Sarcocystis is an intracellular, cyst forming and worldwide distributed parasites. In the present study, fifty five different cuts of imported frozen buffalo meat were collected from different localities of Alexandria markets and were subjected to macroscopic and microscopic examination followed by molecular methods. Polymerase chain reaction used to amplify 18S rRNA gene from the collected samples followed by sequence analysis to detect infections with different Sarcocystis spp. The result revealed that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Cysts were separated from the surrounding muscles and genomic DNA was extracted independently from each of Sarcocystis cysts from the esophagus (five cysts from each province) using the Genomic DNA Extraction Kit (Thermo Fisher Scientific Inc., MA, USA) (24). The concentration of DNA was measured using a spectrophotometer (Thermo Fisher Scientific, USA).…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cysts were separated from the surrounding muscles and genomic DNA was extracted independently from each of Sarcocystis cysts from the esophagus (five cysts from each province) using the Genomic DNA Extraction Kit (Thermo Fisher Scientific Inc., MA, USA) (24). The concentration of DNA was measured using a spectrophotometer (Thermo Fisher Scientific, USA).…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…The concentration of DNA was measured using a spectrophotometer (Thermo Fisher Scientific, USA). PCR reactions were applied using the primer set: forward (5´-GGCCCTTTTAGTGAGGGTGT-3´) and reverse (5´-TACGAATGCCCCCAACTGTC-3´) of the 18SrR-NA gene of S. fusiformis targeting 270bp fragment (24). PCR reactions were performed in a final reaction volume of 25 μL using 2× PCR Master Mix Solution (i-Taq™) (iNtRON Biotechnology, Seoul, Korea).…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the 18S rRNA gene region is more widely used for the identification of Sarcocystis spp. than the other gene regions (4,16,18,23,24,27,33,42). However; it has been reported that S. hominis, S. bovifelis, S. bovini, and S. rommeli species cannot be distinguished by the 18S rRNA gene region, and the term 'S.…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of infection and presence of different developmental cyst merozoite generation phase is regarded due to the contact and graze of the imported cattle for at least 2-3 months in contaminated pasture before slaughtering as a most common prevalent habit among livestock animals' owners in Kurdistan region however the pasture may contain sever amount of shaded oo-sporo/cyst (Fayer 1977;Khoshsima et al 2018). Mousa et al (2016) diagnosed 70% of the frozen meat came from Brazil and India infected with Sarcocystis by molecular techniques.…”
mentioning
confidence: 99%